Treatment of Wastewater Containing Wood Waste Pyroligneous Acid Preservative by Activated Carbon in Rubberwood Manufacturing Process - Othaman, Rizafizah; Susilo, Agus; Habaki, Hiroaki; Egashira, Ryuichi (ASEAN Journal of Chemical Engineering, 2009)
In this paper, the feasibility of using the products from thermal treatment of rubberwood waste, i.e., pyroligneous acid as preservative and activated carbon as adsorbent to treat the wastewater containing the preservative was studied. Firstly, the sawdust was thermally treated under various conditions to produce the pyroligneous acid and the activated carbon. Atmosphere and treatment temperature were a significant factor in determining the yield of the products. Secondly, the equilibrium adsorption runs were carried out with the model wastewater containing single, multi solutes, or the pyroligneous acid and with the activated carbon obtained under steam atmosphere. Phenolic compounds were adsorbed at the highest in single solute solutions, and lower in multi solutes solutions. Finally, the feasibility of this process improvement was discussed.